A Congressman Looks at Agricultural Science Communications - Robert D. Price (Journal of Applied Communications, 1972)
Remarks by Congressman Robert D. Price, Texas, before the National Seminar on Agricultural Science Communication, Washington, D.C., January 26, 1971.